Lifestyle and health determinants of cardiovascular disease among Greek older adults living in Eastern Aegean Islands: An adventure within the MEDIS study - Alexandra Foscolou; Evangelos Polychronopoulos; Efstratia Paka; Stefanos Tyrovolas; Vassiliki Bountziouka; Akis Zeimbekis; Dimitra Tyrovola; Dilek Ural; Demosthenes Panagiotakos (Hellenic Journal of Cardiology, 2016)
Objective: The aim of the present study was to evaluate lifestyle and health determinants of cardiovascular disease (CVD) risk among Greek elderly residents living in Eastern Aegean islands, in both Greece and Turkey. Methods: Under the context of the MEDIS study, 724 older adults (aged 65 to 100 years) from 8 Eastern Aegean Sea Greek islands (n = 100 living in Samothrace, 142 in Lesvos, 150 in Limnos, 76 in Ikaria, 52 in Kassos, 149 in Rhodes and Karpathos) and from Turkey (n = 55 older adults of Greek origin living on Gökçeada Island) were voluntarily recruited. Overall cardiometabolic risk was measured as the sum (range 0-4) of four common CVD risk factors (hypertension, diabetes, dyslipidemia and obesity). Results: Greek islanders had higher CVD scores compared to Greeks of Gökçeada (1.9±1.1 vs 1.4±1.0 risk factors / participant, p<0.001). Further analysis revealed that the diet of Greek islanders was similar to the traditional Mediterranean diet; however, these individuals demonstrated 2-times higher odds (95% CI, 1.04–3.87) for having hypertension, 1.53-times higher odds (95% CI, 0.66–3.54) for having diabetes, 3.29-times higher odds (95% CI, 1.58–6.81) for having hypercholesterolemia; whereas they had 0.78-times lower odds (95% CI, 0.40–1.52) for being obese, compared to elderly Greek adults living on Gökçeada. Conclusions: Overall, CVD risk seems to be low among Eastern Aegean Islanders; certain differences in CVD risk factors exist between Greek islanders and their counterparts living in Gökçeada, and those differences may be attributed to various environmental, cultural and lifestyle factors.